2014
DOI: 10.1038/srep06647
|View full text |Cite
|
Sign up to set email alerts
|

Species sorting during biofilm assembly by artificial substrates deployed in a cold seep system

Abstract: Studies focusing on biofilm assembly in deep-sea environments are rarely conducted. To examine the effects of substrate type on microbial community assembly, biofilms were developed on different substrates for different durations at two locations in the Red Sea: in a brine pool and in nearby bottom water (NBW) adjacent to the Thuwal cold seep II. The composition of the microbial communities in 51 biofilms and water samples were revealed by classification of pyrosequenced 16S rRNA gene amplicons. Together with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 44 publications
9
64
0
Order By: Relevance
“…Biofilms were developed on six different types of materials in the brine pool for 3 and 6 days. The devices for biofilm development has been reported in Zhang et al (2014) and the schematic diagrams are also shown in Figure S1 in the present study. The materials were deployed into the brine pool by the ROV.…”
Section: Methodssupporting
confidence: 55%
See 2 more Smart Citations
“…Biofilms were developed on six different types of materials in the brine pool for 3 and 6 days. The devices for biofilm development has been reported in Zhang et al (2014) and the schematic diagrams are also shown in Figure S1 in the present study. The materials were deployed into the brine pool by the ROV.…”
Section: Methodssupporting
confidence: 55%
“…This brine pool is located at a depth of approximately 850 m and is characterized by a high concentration of potential electron acceptors such as nitrate (18.5 mg L −1 ) and sulfate (2.7 g L −1 ). The particulate organic carbon (POC) concentration was 3.5 mg L −1 which was 10 times greater than that of the adjacent normal deep-sea water (NDW) (Zhang et al, 2014, 2015). In contrast, methane and hydrogen sulfide were depleted with respect to NDW.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…To create the THP-1 conditioned medium, 4 l of a 2 mM fibrillar A␤ [25][26][27][28][29][30][31][32][33][34][35] (Tocris) suspension was added to 24-well plates and allowed to air-dry. THP-1 cells were subsequently plated on the A␤-coated wells at a density of 20,000/well in Neurobasal medium.…”
mentioning
confidence: 99%
“…DNA Extraction, 16S rRNA Gene Amplification, and Sequencing-DNA extraction was performed as described previously (25). Briefly, the cultured bacterial cells were pelleted by centrifugation at 4000 ϫ g for 10 min and then lysed with lysozyme, proteinase K, and 10% SDS.…”
mentioning
confidence: 99%